Phenomenology and the history of philosophy - Leško, Vladimír; Bęben, Dariusz (Folia Philosophica, 2012)
Even though Husserl himself did not write on the history of philosophy in true sense, his work is in fact a peculiar dialogue with philosophical tradition - from rejection to almost complete acceptance. What distinguishes Husserl’s research in this area is its full subordination to phenomenological reflection. His views are revised by Eugen Fink, who (with reference to Heidegger) claims that man, while living within the history, is unconditionally subordinated to it. Hence, Fink bases his philosophy in a claim that man exists historically on account of worldly rule of separation and division in both labour and fight. Jan Patočka’s work in turn, offers an unusual synthesis of historico-philosophical reflection and asubjective phenomenology. This is one of the reasons for which it has prominent place in history of phenomenological movement. Patočka is maybe the first philosopher in 20th century who, in confrontation with Hegel’s profound model, engaged openly in analysis of philosophy of the history of philosophy.